f'(x)= sec x tan x is correct
now use the product rule
f''(x) = secx(sec^2x) + tanx(secx)(tanx)
= sec^3 x + secx(tan^2x)
I will leave the subbing to you
If f(x)= sec x, find f"(Pi/4)
I am not sure how to take the 2nd derivative?
f'(x)= sec x tan x
f"(x)=???
Is it f"(x)= (sec x tan x)(sec^2x)???
Please Help!
3 answers
What do you mean subbing? I thought that was the final answer? In the book it leaves f"(x)= - cos x for f(x)= cos x
Oops, sorry about that. Do you mean this:
sec^3(Pi/4) + sec(Pi/4)(tan^2(Pi/4)) =
3*sqrt(2)
sec^3(Pi/4) + sec(Pi/4)(tan^2(Pi/4)) =
3*sqrt(2)